KAJIAN ATMOSPHERE PASAR TRADISIONAL: PERSPEKTIF ARSITEKTUR - Wongso, Jonny; Tela, I Nengah; Hadi, Zuriyon; Yeza, Riska Nofri; Anief, Bahrul; Ilona, Desi; Zaitul, Zaitul (Fakultas Teknik, Universitas Riau Kepulauan, 2024)
Market atmosphere is an important aspect that must be considered by architects, market managers, and traders so that buyers feel comfortable and safe in the market. The market atmosphere will have an impact on the interests and behaviour of buyers. Previous research on market atmosphere failed to pay attention to traditional markets. The traditional market is still an important medium interaction for social and cultural gatherings and meeting demand and supply. This study aims to describe the atmosphere component of a traditional shop/market in Painan, Pesisir Selatan Regency. Using six components identified through a comprehensive literature review: Market cleanliness, Market scent, Air conditioning, Lighting, Colouring, and the appearance and layout of the building. Buyers in the market are used as respondents. Research data is primary data obtained through surveys. The analysis method uses descriptive and comparative analysis methods. A total of 71 buyers participated in this study. The results showed that the atmosphere of traditional shops/markets was inadequate both from the components of cleanliness, smell, air conditions, lighting, colouring, and the appearance and layout of the building. After testing the difference between sex and education level, only one component significantly differed between men and women (lighting) and education level (colouring). The research suggests that the government should revitalize the Painan traditional market into a highly attractive market to remain competitive in the era of the industry revolution 4.0.